2018
DOI: 10.1111/pai.12854
|View full text |Cite
|
Sign up to set email alerts
|

Cow's milk allergic children—Can component‐resolved diagnostics predict duration and severity?

Abstract: Oral food challenge cannot be replaced by s-IgE to whole milk protein or milk components nor SPT in the diagnosis of CMA; however, high levels of milk components and s-IgE to milk increase the risk of a long-lasting or persisting CMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Milk component proteins have been previously shown to have some utility in identifying patients with persistent or more severe cow's milk allergy, 38 and baseline levels of IgE specific to milk, caseins, and b-lactoglobulin had significant association with SU outcome of MOIT when adjusted for the adjuvant treatment group. 17 However, the epitope-specific IgE model outperformed the best model using only standard laboratory data (ie, SCP-specific IgE, IgG, and IgG 4 ; AUC 5 0.80 and accuracy 5 80%).…”
Section: Discussionmentioning
confidence: 99%
“…Milk component proteins have been previously shown to have some utility in identifying patients with persistent or more severe cow's milk allergy, 38 and baseline levels of IgE specific to milk, caseins, and b-lactoglobulin had significant association with SU outcome of MOIT when adjusted for the adjuvant treatment group. 17 However, the epitope-specific IgE model outperformed the best model using only standard laboratory data (ie, SCP-specific IgE, IgG, and IgG 4 ; AUC 5 0.80 and accuracy 5 80%).…”
Section: Discussionmentioning
confidence: 99%
“…For example, children with higher levels of IgE to cow's milk allergens in PAMD@ had a higher risk for persisting milk allergy. 178 Using PAMD@, the IgE/IgG4 ratio and the sIgE sensitization pattern allowed the discrimination of patients with cow's milk allergy who tolerate cooked milk. 179 However, further PAMD@ studies are needed to predict tolerance, with the hope of being able to reduce the need for food challenges.…”
Section: Milkmentioning
confidence: 99%
“…36 Component-resolved diagnostics are promising tools for diagnosing FA and may predict duration and severity of cow's milk allergy. 37 In 78 children, it was found that OFC cannot be replaced by sIgE to whole milk protein or milk components nor skin prick tests in the diagnosis of cow's milk allergy. However, high levels of milk components and sIgE to milk increase the risk of a long-lasting or persisting cow's milk allergy.…”
Section: Food Challengesmentioning
confidence: 99%